Relationship between renalase and N-terminal pro-B-type Natriuretic Peptide (NT pro-BNP) in haemodialysis patients - Marcin Dziedzic; Beata Petkowicz; Anna Bednarek-Skublewska; Janusz Solski; Agnieszka Buczaj; Piotr Choina (Annals of Agricultural and Environmental Medicine, 2014)
Introduction. Our knowledge in the field of cause of deaths in dialysis patients is rapidly expanding, yet we still do not fully understand how renalase regulates the processes of cardiovascular disease developing in end-stage renal disease. Increased sympathetic nerve activity observed in chronic kidney diseases due to raised catecholamines in plasma results from the absence of renalase. Renalase synthesized and secreted by the kidneys participate in the regulation of sympathetic tone and blood pressure. A family of natriuretic peptides has been identified – NT pro-BNP – which seems to be the best predictor of clinical outcome and marker of extracellular fluid overload, as well as predicting mortality, irrespective of renal function. Objective. The aim of the presented study was to investigate renalase concentration and investigate associations between NT-proBNP, as well as analyzed parameters in haemodialysis patients. Materials and method. The study was conducted among residents of the municipality and neighbouring villages in the province of Lublin, central-eastern Poland. 49 male subjects on haemodialysis, aged 65.3 ± 14.2 years, median time on haemodialysis: 37.5 months, were included. All study subjects underwent haemodialysis 3 times a week. The mean concentration of renalase in the entire study population was 126.59 ± 32.63 ng/mL. The circulating levels of NT-proBNP was 813.64 ± 706.96 pg/mL. A significant inverse correlation was found between NT-proBNP and renalase plasma levels (R = –0.3, P = 0.03). Conclusions. Inverse correlation between NT-proBNP and renalase plasma levels in haemodialysis patients were due to impaired kidney function, accompanied by increased sympathetic nerve activity, which have an impact on the development of hypertension and cardiovascular complications.